Impact of photo-treatment on tomato physiological qualities during storage and on-shelf display - Offiong, Ubong; Jamaludin, Diyana; Nakasha, Juju; Khairudin, Nurulhuda (Universiti Malaysia Perlis, 2023)
Tomato's short shelf life and economic significance resulted in its classification as a model for studying the physiological behavior of fruits and vegetables. This study employs light treatment to investigate the effect of various light spectrums on tomatoes' physiological qualities. Four light treatments, white LED, 5R:1B LED, 5B:1R LED , and the control (without light treatment) were placed under a storage condition with a temperature of 5ºC and relative humidity of 88% for 5 days and an on-shelf display condition of 22ºC and relative humidity of 78%. Response variables were colour changes, firmness, total soluble solids, and pH. It was observed that 5R:1B LED significantly increase red colour development in tomatoes during storage and on-shelf display condition, promoting lycopene accumulation, while 5B:1R LED delays red colour accumulation during storage but rather prolong pale-yellow colour development during shelf display condition, promoting ζ- carotene and xanthophyll accumulation. Tomatoes treated with 5B:1R and white LED enhance tomato firmness more than the control samples during storage and on-shelf display. 5B:1R LED reduces the pH of tomatoes significantly, making them more acidic and resistance to microbes, while 5R:1B enhances the sugar accumulation of tomatoes. This makes photo-treatment a sustainable technique for tomato physiological quality preservation and senescence postponement.